Analisis Ketenagakerjaan Sektor Industri di Provinsi Aceh Kawasan Barat Selama Periode 2019-2023 - Marzalina, Marzalina; Haryani, Haryani; Mangkuwinata, Denny Sumantri (Singkite Journal, 2025)
Research was conducted in the Aceh Province, Western Region, for the period 2019-2023. With a study of labor in the industrial sector and the rate of Gross Regional Domestic Product (GRDP). Analysis was carried out on panel data from BPS Aceh sources, using the Ordinary Least Square (OLS) method. Based on data fluctuations, the modeled results are Y = 316.75 + 71.82X, which means that every increase in the GDPR rate of the industrial sector will increase the number of workers. The relationship between the number of industrial sector workers and the GDP rate is 18%. Even though it is still considered small, it is quite a significant aspect of the growth of the industrial sector in the Aceh West Region.